Are over-paid Chief Executive Officers better innovators? - Habib Jouber (Journal of Economics, Finance and Administrative Science, 2013)
This paper focuses on the pay level of the highest paid executive directors, which we label as “Executive Director's Organizational Level” (henceforth EDOL), to raise the question if highest paid CEOs invest heavily in innovative projects. Two-stage least squares (2SLS) regressions show that over-paid CEOs are more likely to invest in R&D projects. They highlight, moreover, both from a “statutory” and an “activist” perspective, that CEOs' intends to invest in value-enhancing innovations are contingent upon compensation committee independence and investor protection level. Check tests reveal that the pay-performance “innovation” effect for option-based compensation is higher than that for stock-based compensation. Within the options (stocks) rewards, unvested options (restricted stocks) are the most effective. However, we find that over-paid CEOs of low-growth firms achieve less innovation compared to those of high-growth firms. Throughout, we reveal that the effect of CEOs performance-pay on innovation is mainly relevant among overconfident managers than non-overconfident ones. – – El presente artículo se basa en el nivel salarial de los directores generales que más cobran, y hemos denominado “Nivel Organizativo de Director General” (en adelante, NODG) a fin de responder si los directores generales mejor remunerados invierten más en proyectos de innovación. Las regresiones de mínimos cuadrados en dos fases demuestran que los directores generales mejor remunerados son más proclives a invertir en proyectos de I y D. Dichas regresiones destacan, tanto desde una perspectiva “reglamentaria” como desde una “activista”, que la intención de los directores generales de invertir en innovaciones con valor a\~nadido están supeditadas a la independencia del comité de compensación y al nivel de protección del inversor. Las pruebas de control revelan que el efecto “innovación” en el sueldo-rendimiento para la remuneración con base en acciones es superior al de la remuneración con base en opciones. Dentro de los incentivos en acciones, aquellas sin derecho de posesión (acciones restringidas) son las más efectivas. No obstante, observamos que los directores generales mejor pagados en las empresas de bajo crecimiento consiguen menos innovación que aquellos de las empresas con un mayor crecimiento. En todo momento, hemos observado que el efecto sueldo-rendimiento de los directores generales sobre la innovación es mucho más marcado entre los jefes con gran confianza en sí mismos.
Keywords: G30; G32; M41; 330; Chief Executive Officer compensation; Executive Director's Organizational Level; Research and Development expenditures; Patents; Patent citations; Remuneración del director general; Nivel Organizativo de Director General; Gasto en investigación y desarrollo; Patentes; Citas de patentes